(untitled) (Journal of Medical & Health Sciences Review, 2025)
Mastacembelus armatus is an important freshwater spiny eel locally recognized as Bam. This fish is liked by many people of the world for its attractive flavor and comparatively tough texture. The current experiment was designed to enumerate the relationship between length- weight and condition factor for spiny eel accordingly. Collection of samples were done from district Badin Sindh Pakistan during three Months from March to May 2018. The total ninety specimens ranged from smallest fish 28.5cm and larger fish about 51.3 cm in length and from 56.5g to 246.5 g in weight procured from the local fishermen. The coefficients of correlation were calculated by methods of LeCren (1951) resulted in the equation given below: Log w = -3.20 + 3.10 (male) Log w = -3.26 + 3.21 (female) and Log w = -3.0 + 3.15 (combined), finally it was decided that the length-weight equation exhibited positive allometric type of growth of Mastacembelus armatus from District Badin, Sindh.